2016
DOI: 10.1016/j.chb.2016.03.047
|View full text |Cite
|
Sign up to set email alerts
|

“I like them, but won't ‘like’ them”: An examination of impression management associated with visible political party affiliation on Facebook

Abstract: Unlike traditional media, our interactions with political parties via social media are generally public, subject to scrutiny by others and, consequently, a self-presentation concern. This paper contributes to theory on impression management within social network sites (SNSs) by providing an understanding of the effect of visible affiliation on page 'Liking' behavior in the context of political parties; specifically, the possible association with social anxiety and the use of protective impression management. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 46 publications
(56 reference statements)
3
46
0
1
Order By: Relevance
“…The option to inconspicuously 'like' a political brand's Facebook page, would eliminate the risk of projecting an undesired social-self, but would allow the potential advantages such as entertainment, information or identity affirmation for the user and a means of direct communication for marketers (Macafee 2013;Hanson et al 2010). Prior work by Marder et al (2016) found electorates had a higher intention to inconspicuously 'Like' compared to when this was conspicuous. However, this did not investigate the role of the undesired social-self in this difference in intention over two visibility conditions.…”
Section: H3: the Relationship Between Proximity To The Undesired Socimentioning
confidence: 99%
See 4 more Smart Citations
“…The option to inconspicuously 'like' a political brand's Facebook page, would eliminate the risk of projecting an undesired social-self, but would allow the potential advantages such as entertainment, information or identity affirmation for the user and a means of direct communication for marketers (Macafee 2013;Hanson et al 2010). Prior work by Marder et al (2016) found electorates had a higher intention to inconspicuously 'Like' compared to when this was conspicuous. However, this did not investigate the role of the undesired social-self in this difference in intention over two visibility conditions.…”
Section: H3: the Relationship Between Proximity To The Undesired Socimentioning
confidence: 99%
“…Drawing from Marder et al (2016) our underlying notion is that social anxiety mediates the relationship between the increased proximity to the undesired social-self and the intention to conspicuously 'like' a political brand's Facebook page as follows.…”
Section: H2: Increased Proximity To the Undesired Social-self Is Negamentioning
confidence: 99%
See 3 more Smart Citations